Aid administration and sustainable development in post-COVID-19 era in Africa: a review of literature approach - Gamel Abdul-Nasser Salifu; Zubeiru Salifu (Cogent Social Sciences)
This paper contributes to the ongoing discourse surrounding aid administration for sustainable development in the post-COVID-19 era. African economies experienced a 1.5% contraction during this period, leading to a 35.85% increase in the number of people living in poverty. The paper addresses the crucial question of aid effectiveness in light of these challenges. Utilizing a systematic review approach, we examine existing studies and identify gaps in the literature related to aid effectiveness. Our analysis focuses on a sample of 84 highly cited peer-reviewed articles from the Web of Science (WoS) database spanning the years 2003–2023. The findings reveal a trend where international donors allocate aid to numerous African countries characterized by weak governance and leadership structures. Consequently, a sizable portion of aid funds fails to reach the intended beneficiaries due to the complex challenges associated with aid administration. In response to these challenges, we advocate the adoption of comprehensive frameworks to monitor rent-seeking behaviour, which often hampers economic growth. This approach aims to address issues of embezzlement by local elites, who disproportionately receive funds on behalf of their constituencies. This will ensure that every allocated dollar of aid reaches its designated recipients. This study is distinct in its contribution by offering insights into various frameworks for aid administration while laying the foundation for improved aid management in transitional economies by providing valuable knowledge to enhance the effectiveness of aid initiatives.